The Isolation Of Kojic Acid Producing Fungi And The Optimization Of Kojic Acid Production - Md Salleh, Madihah (1996)

(untitled)
A local strain of fungus, which was found to be a high kojic acid producer has been isolated from Morning glory flower (Bixa orellana) using glucose-peptone medium. The pure strain was obtained through several steps of monospore isolation procedures using spread plate technique and identified by International Mycological Institute as Aspergillus flavus Link.Optimization of medium composition and cultural conditions for kojic acid production by this fungus were carried out in shake flask. The development of dissolved oxygen tension (DOT) control strategies aimed at improving kojic acid production by this strain was carried out using 1.5 L stirred tank reactor with automatic pH and DOT control systems. Initial culture pH 3 was found to POLO be optimum for kojic acid production. This strain was able to grow and produce kojic acid in various carbon sources such as glucose, starch, sucrose and xylose. However, the highest production of kojic acid was obtained at 100 g/L (w/v) glucose. In addition, 5 g/L of yeast-extract was found to be the best nitrogen source for fungal growth and enhancement of kojic acid production. Addition of 4% (v/v) of methanol to glucose yeast-extract medium increased kojic acid production by two times. The optimized medium for kojic acid production for this strain was proposed and the medium consisted of 100 g/L glucose, 1.0 g/L KH2PO4,0.5 g/L MgSO4. 7H20, 5.0 g/L yeast-extract and 4% methanol. Using this optimal medium the maximum kojic acid production in batch fermentation using shake flask was 39 g/L. This fermentation gave yield and productivity of 0.04 g/g and 0.07 g/L/h, respectively and is comparable to that reported in the literature for industrial strain. The DOT control strategy for the improvement of the kojic acid production by this strain was also developed. By controlling DOT at 80% saturation during growth phase and then switched to 30% saturation during production phase, increased the production of kojic acid by about two times as compared to uncontrol fermentation in the stirred tank fermenter which only produced maximum concentration of kojic acid of 15 g/L.. The effect of the addition of yeast-extract during the fermentation was also investigated using a constant fed-batch culture. The addition of 15 g/L yeast-extract at constant flow rate of 3.2 ml/h during the production phase caused excessive mycelial growth and decreased kojic acid production.